Mechanisms and Management of Itch in Dry Skin - Catharina Sagita Moniaga; Mitsutoshi Tominaga; Kenji Takamori (Medical Journals Sweden, 2020)
Chronic itch is a burdensome clinical problem that often accompanies pathological dry skin-based conditions, such as atopic dermatitis, and systemic disorders, such as kidney diseases, with an unclear pathomechanism and treatments. One of the basic mouse models to investigate mechanisms of itch associated with dry skin is a mixture of acetone and ether followed by water. Animal studies using the acetone and ether followed by water model have revealed that many mediators and receptors, e.g. mas-related G protein-coupled receptor family, transient receptor potential, and chemokines, are responsible for itch and its hypersensitivity, supporting the hypothesis that dry skin-induced itch is a histamine-independent pathway. New insights have been acquired into the interplay between neurones and non-neuronal cells in the initiation, modulation, and sensitization of itch. Several therapeutic options for itching have thus been developed. This review summarizes the updated pathogenesis and therapeutic strategies for itch in dry skin conditions.